Hidden persuaders in cocoa and chocolate : a flavor lexicon for cocoa and chocolate sensory professionals - Januszewska, Renata (Woodhead Publishing, an imprint of Elsevier, 2018)
Flavors can be seen as hidden persuaders in the consumer decision making process, so understanding flavors and how consumers are triggered by them is critical in the research and development of new products. Hidden Persuaders of Cocoa and Chocolate provides an overview of the tastes, aromas and notes describing cocoa and chocolate. In addition to exploring tastes, aromas, and notes, the book broadens the language for describing chocolate by storytelling about ingredients including relating the tasting experience to "pairing flavors." This resource, designed for both academics and those working in research and development, equips the reader with the language to describe the sensory attributes, for the purposes of new product development or (sensory) quality improvement. --Back cover